An Application of Reflective Practice to Nursing Practicum - Chaiyarit, Arunee; Jangsombatsiri, Wimol (วารสารสันติศึกษาปริทรรศน์ มจร, 2017)
Reflective practice is a significant procedure to promote nursing professional development and to enhance levels of quality care in nursing students. With respect to the process of reflective practice, self-perception of nursing students can help these students to provide effectiveness in caring for patients. Additionally, nursing students should know about patients, families and their environment. Nursing students can use these data to plan for effective care to the patient. Self-perception of nursing students leads these students to have mindfulness. Furthermore, theses students can consider all aspects of patient problems. Also, nursing students can have humanistic care for the patient. In Addition, nursing students should understand the behavior of the patient because all patient behaviors have the meaning and these behaviors represent for response of the patient to illness and affect to treatment and care. Mindfulness and deeply consideration to reflect experience of nursing students can help these students to analyze and plan for caring to the patient that can improve the patient health status. This paper focuses on the significant of reflective practice, the use of reflective practice in nursing practicum, technique of reflective practice for nursing students, and summarization for interested person for further searching.